How well do we recognise non-motor symptoms in a British Parkinson's disease population? - Hu, M; Cooper, J; Beamish, R; Jones, E; Butterworth, R; Catterall, L; Ben-Shlomo, Y (2011)
Although awareness of non-motor symptoms in Parkinson's disease (PD) has recently increased, little is known about their recognition and treatment in routine clinical practice. We therefore applied non-motor rating scales for dementia, depression, anxiety and excessive daytime sleepiness to a community-ascertained cohort of 202 PD patients. Hospital case notes were reviewed for evidence that the non-motor problems had been recognized and whether any action had been taken to ameliorate or assess these symptoms. The prevalence of each non-motor problem was as follows: dementia 25.3% (95% CI 19.0, 32.4), depression 37.3% (95% CI 30.6, 44.4), anxiety 31.3% (95% CI 25.0, 38.2), excessive daytime sleepiness 59.4% (95% CI 52.2, 66.3). However, these features were only recognised in 27.2, 38.7, 9.5, and 12.8%, respectively. We did not identify any specific factor that predicted under-recognition. Our study shows that when rating scales are applied to formally assess for non-motor symptoms a large clinical 'iceberg effect' emerges with the majority of symptoms going unrecognised and untreated.